Delayed treatment of secondary degeneration following acute optic nerve transection using a combination of ion channel inhibitors - Yates, N.; Giacci, M.; O Hare Doig, R.; Chiha, W.; Ashworth, B.; Kenna, J.; Bartlett, C.; Fitzgerald, Melinda (Medknow Publications and Media Pvt. Ltd., 2017)
Studies have shown that a combined application of several ion channel inhibitors immediately after central nervous system injury can inhibit secondary degeneration. However, for clinical use, it is necessary to determine how long after injury the combined treatment of several ion channel inhibitors can be delayed and efficacy maintained. In this study, we delivered Ca 2+ entry-inhibiting P2X7 receptor antagonist oxidized- ATP and AMPA receptor antagonist YM872 to the optic nerve injury site via an iPRECIO @ pump immediately, 6 hours, 24 hours and 7 days after partial optic nerve transection surgery. In addition, all of the ion channel inhibitor treated rats were administered with calcium channel antagonist lomerizine hydrochloride. It is important to note that as a result of implantation of the particular pumps required for programmable delivery of therapeutics directly to the injury site, seromas occurred in a significant proportion of animals, indicating infection around the pumps in these animals. Improvements in visual function were observed only when treatment was delayed by 6 hours; phosphorylated Tau was reduced when treatment was delayed by 24 hours or 7 days. Improvements in structure of node/paranode of Ranvier and reductions in oxidative stress indicators were also only observed when treatment was delayed for 6 hours, 24 hours, or 7 days. Benefits of ion channel inhibitors were only observed with time-delayed treatment, suggesting that delayed therapy of Ca 2+ ion channel inhibitors produces better neuroprotective effects on secondary degeneration, at least in the presence of seromas.